2017
DOI: 10.1364/oe.25.024658
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate critical coupling in all-dielectric metasurface absorbers

Abstract: We develop the theory of all-dielectric absorbers based on temporal coupled mode theory (TCMT), with parameters extracted from eigenfrequency simulations. An infinite square array of cylindrical resonators embedded in air is investigated, and we find that it supports two eigenmodes of opposite symmetry that are each responsible for half of the total absorption. The even and odd eigenmodes are found to be the hybrid electric (EH) and hybrid magnetic (HE) waveguide modes of a dielectric wire of circular cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…As can be observed, both the resonance frequency (open red triangles in Figure a) and the material loss rate (open purple triangles in Figure b) for the odd eigenmode show a strong dependence on fluence in comparison to the even eigenmode. Indeed, prior studies have shown that the odd eigenmode is about three times more sensitive to changes in height than the even eigenmode . We thus conclude that since the top photodoping is dominant in the study presented here, the optical excitation primarily affects the effective height of the all‐dielectric array, and thus chiefly alters the odd eigenmode.…”
supporting
confidence: 45%
See 2 more Smart Citations
“…As can be observed, both the resonance frequency (open red triangles in Figure a) and the material loss rate (open purple triangles in Figure b) for the odd eigenmode show a strong dependence on fluence in comparison to the even eigenmode. Indeed, prior studies have shown that the odd eigenmode is about three times more sensitive to changes in height than the even eigenmode . We thus conclude that since the top photodoping is dominant in the study presented here, the optical excitation primarily affects the effective height of the all‐dielectric array, and thus chiefly alters the odd eigenmode.…”
supporting
confidence: 45%
“…Thus, for example, a different type of all‐dielectric metasurface—an absorber—may be fashioned through incorporating a small amount of material loss in the resonators. The specific value of dielectric loss necessary to achieve peak absorption is determined by balancing the radiative dissipation—set by the geometrical parameters—and the material dissipation loss at the resonant frequency . This optimal state is termed degenerate critical coupling and realizes a total quality factor (Q‐factor) of 1/4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic wave absorbers may alternatively be fashioned from all‐dielectric metasurfaces, which consist of arrays of high permittivity geometrical shapes (cubes, spheres, cylinders, etc. ), and realize Mie resonances, permitting them to achieve novel electromagnetic responses .…”
Section: Comparison Of the Scattering Matrix Properties Of The Zero‐rmentioning
confidence: 99%
“…Dielectric resonators may support a large number of different types of resonances, and here we utilize electric and magnetic quasi‐dipole and multipole modes, which have been shown to be equivalent to hybrid waveguide modes in dielectric materials . Notably, the lowest order hybrid waveguide modes (i.e., HE 111 and EH 111 modes) have been shown to be the even‐eigenmode (electric dipole) and odd‐eigenmode (magnetic dipole) of the resonator, when the structure possesses mirror symmetry with respect to a perpendicular plane at the midpoint of its directrix . A key feature of the cylindrical geometry is that the center frequency ω 0 of each eigenmode can be tuned as a function of height (odd eigenmode) and diameter (even eigenmode).…”
Section: Comparison Of the Scattering Matrix Properties Of The Zero‐rmentioning
confidence: 99%